Chronic Kidney Disease in Brazil: Current Status and Recommended Improvements - Andrea Carla Bauer; Rosilene M. Elias; Hugo Abensur; Marcelo Costa Batista; Angela Marie Jansen; Miguel Carlos Riella (Karger Publishers, 2024)
Background: Over the last 3 decades, over 700 million individuals worldwide have been diagnosed with chronic kidney disease (CKD). In a 2017 survey in southern Brazil, 11.4% of those surveyed had CKD. Early identification and effective therapy in Brazil may reduce CKD's impact. This panel discusses the early diagnosis and treatment of CKD and the barriers and actions needed to improve the management of CKD in Brazil. A panel of Brazilian nephrologists was provided with relevant questions to address before a multiday conference. During this meeting, each narrative was discussed and edited through several rounds until agreement on the relevant topics and recommendations was achieved. Summary: Panelists highlighted hurdles to early diagnosis and treatment of CKD. These include, but are not limited to, a lack of public and patient education, updated recommendations, multidisciplinary CKD treatment, and a national CKD database. People-centered, physician-centered, and healthcare institution-centered actions can be taken to improve outcomes. Patient empowerment is needed via multiple channels of CKD education and access to health-monitoring wearables and apps. Primary care clinicians and nonspecialists must be trained to screen and manage CKD-causing illnesses, including diabetes and hypertension. The healthcare system may implement a national health data gathering system, more screening tests, automated test result reporting, and telehealth. Key Messages: Increasing access to early diagnosis can provide a path to improving care for patients with CKD. Concerted efforts from all stakeholders are needed to overcome the barriers.